2016
DOI: 10.1371/journal.pone.0165454
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Enzyme Responses Induced by Whiteflies in Tobacco Plants in Defense against Aphids: Catalase May Play a Dominant Role

Abstract: BackgroundBemisia tabaci MEAM1 (Middle East-Asia Minor 1) feeding alters antioxidative enzyme activity in some plant species. Infestation of B. tabaci nymphs decreases Myzus persicae performance on systemic, but not local leaves of tobacco plants. However, it is unclear if B. tabaci nymphs induced antioxidant activities contributing to the aphid resistance.Methodology/Principal FindingsWe investigated the relationship between antioxidants induced by nymphs of B. tabaci feeding on tobacco and aphid resistance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 85 publications
(103 reference statements)
2
20
0
4
Order By: Relevance
“…In the available literature on the topic of the relationships between the activity of antioxidating enzymes and antioxidant content in plants, which were previously changed as a result of the stress factors, information on the infestation of plants by aphids is very scarce, and with respect to contaminants, there is no data at all. In their analysis of the relationship between antioxidants induced by nymphs of B. tabaci feeding on tobacco and aphid resistance, Zhao et al [22] point at CAT as the main enzyme responsible for inducing tobacco resistance to aphids. Next, He et al [21] indicated SOD and POD as the enzymes responsible for the resistance of two varieties of chrysanthemum to aphids.…”
Section: Discussionmentioning
confidence: 99%
“…In the available literature on the topic of the relationships between the activity of antioxidating enzymes and antioxidant content in plants, which were previously changed as a result of the stress factors, information on the infestation of plants by aphids is very scarce, and with respect to contaminants, there is no data at all. In their analysis of the relationship between antioxidants induced by nymphs of B. tabaci feeding on tobacco and aphid resistance, Zhao et al [22] point at CAT as the main enzyme responsible for inducing tobacco resistance to aphids. Next, He et al [21] indicated SOD and POD as the enzymes responsible for the resistance of two varieties of chrysanthemum to aphids.…”
Section: Discussionmentioning
confidence: 99%
“…La presencia de T. vaporariorum en gerbera ha sido documentada por varios autores (Berndt y Meyhöfer, 2008;Parrella et al, 2014;Rojas et al, 2018). La variación en la respuesta entre genotipos pudiera atender a diferencias en características morfológicas de las plantas, las cuales pueden actuar como barreras físicas a los insectos (Taggar y Gill, 2012; Belete, 2018) y a factores relacionados con el metabolismo de las plantas y mecanismos antioxidantes tales como la participación de metabolitos secundarios (Zhang et al, 2017) y la actividad de ciertas enzimas (Taggar et al, 2014;Zhao et al, 2016). A este respecto, estudios en gerbera, destacan la variación entre genotipos en la síntesis de metabolitos secundarios como respuesta al ataque de plagas (Krisps et al, 2001), los cuales constituyen un elemento de importancia para su aprovechamiento en el desarrollo de variedades resistentes (Broekgaarden et al, 2011;Mitchell et al, 2016;Hoshino et al, 2017).…”
Section: Incidencia De Trialeurodes Vaporariorumunclassified
“…Resultados similares a esta investigación sobre el incremento de la actividad enzimática de la POX con la incidencia de la mosca blanca se obtuvieron en genotipos de lenteja negra (Vigna mungo L.) afectados por Bemisia tabaci, donde aquellos más resistentes al estrés por el insecto mostraron un mayor incremento en AePOX que aquellos susceptibles (Taggar et al, 2014). Zhao et al (2016) reportaron un incremento en la actividad enzimática de POX y catalasa en plantas de tabaco después de la presencia de B. tabaci, en comparación de las plantas control. Por otro lado, la capacidad de Mor de promover la AePOX con la alta incidencia de T. vaporariorum, sugiere la participación de la enzima como mecanismo de defensa.…”
Section: Actividad Enzimática De Las Peroxidasas (Aepox)unclassified
See 2 more Smart Citations